Demographic characteristics, aetiology, and assessment of treatment options in leukocytoclastic vasculitis - Cakiter, Alkim Unal; Kucuk, Ozlem Su; Ozkaya, Dilek Biyik; Topukcu, Bugce; Onsun, Nahide (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Vasculitides are a heterogeneous group of diseases characterized by inflammation of the blood vessel walls. Etiological factors include infections, drugs, connective tissue diseases, and malignancies. Aim : To examine the demographic characteristics, etiological factors, and treatment options in 75 patients with leukocytoclastic vasculitis. Material and methods : The study included 75 patients diagnosed with leukocytoclastic vasculitis at our clinic. The patients’ medical records were reviewed to determine their age, sex, presence of systemic symptoms, possible etiological factors, laboratory results, types of cutaneous lesions, locations of the lesions, treatment options, and disease course. Results : There were 43 women and 32 men. Cutaneous lesions affected only the lower limbs in 60 of the 75 patients (80%) and usually presented as palpable purpura (64%, n = 48). Arthralgia (26.7%, n = 20) was the most frequent extracutaneous symptom. Of the patients with secondary vasculitis, the most common causes were infections and drugs. The mean age of the patients with Henoch-Schönlein purpura was 26.8 years. There was no significant association between age and renal, gastrointestinal, or joint involvement. Conclusions : The most common form of vasculitis in our study was cutaneous leukocytoclastic vasculitis. In most of the patients it appeared to be idiopathic. Among drugs, antibiotics were the most common etiological factor. In 4 patients, the cutaneous leukocytoclastic vasculitis behaved like the paraneoplastic syndrome.